Employee Engagement Group Rumah Makan di Yogyakarta Tahun 2024 - Suhartono Suhartono; Awal Satrio Nugroho (Sekolah Tinggi Teknologi Kedirgantaraan, 2026)
Human resources are a very important asset for companies. Good human resource management will produce good results for the company. Employee engagement is a relatively new term in human resource management. According to Tritch [1], employees who have engagement values are workers who are fully involved and enthusiastic in their work. Another view of employee engagement is expressed by Macey & Schneider [2], who state that employee engagement not only makes employees contribute more, but also makes them more loyal, thereby reducing their desire to leave the company voluntarily. Thomas [5] defines employee engagement as a stable psychological state resulting from the interaction between an individual and the environment in which they work. The factors or aspects that shape employee engagement, which are popularly developed by the Kenexa Employee Engagement Index (EEI) standard, are measured based on four components, namely Pride, Satisfaction, Advocacy, and Retention. The research population consists of all 330 employees of a restaurant group in Yogyakarta. This research is referred to as a population study because the entire population is used as the research sample [6]. Therefore, in this study, all employees will be the research sample (all employees will be given a questionnaire).